USING HUMOR IN TEACHING: DOES IT IMPROVE LEARNING - Safarova Malika Kamoliddin qizi; Dilfuza Khudaykul kizi Iskandarova (World Scientific Research Journal, 2025)
This study explores the effect of humor-included methods in teaching and how effective this can be. While humor is used to make the lessons and the atmosphere more engaging, the way it affects the comprehension, retention, and engagement still remains a topic of debate. The research investigates the influence of humors in psychological and emotional sides of learning by the help of analysis that was gained from both teachers and students. According to findings, humor is able to affect the quality of learning positively only if it is applied in a proper way, it also motivates a student, aiding in information retention. Nevertheless, using the humor more than enough or inappropriately in lessons, it can have contradictory effects. This paper makes conclusions with recommendations for educators on the strategic usage of humor to benefit those who are engaged in teaching maximally. In addition, it studies the cultural implications of humor in different classrooms and provides an in-depth discussion on the theoretical settings supporting the use of humor in teaching.